Investigating risk factors of hemorrhagic fever of renal syndrome (HFRS) in Qingdao, Shandong province, China - Ying Li; Jing Jia; Runze Lu; Liyan Dong; Lizhu Fang; Litao Sun; Zongyi Zhang; Qing Duan; Lijie Zhang; Kunzheng Lv; Huilai Ma (PLoS ONE, 2025)
Background Qingdao, a historically high-risk area for hemorrhagic fever with renal syndrome (HFRS) in China, is undergoing agricultural mechanization and urbanization. However, the specific risk factors for HFRS in this context remain unclear. This study sought to determine the risk factors for HFRS in Qingdao. Methods Community-based, 1:2 case-control study. Each case was matched with two healthy neighborhood controls based on biological sex, age, and the same neighborhood or village. Univariate and multivariate conditional logistic regression analyses were performed. Furthermore, stratified analyses were performed to explore risk factor heterogeneity between the peak season for Hantaan virus (HTNV) type HFRS (October-January) and other months. Results 93 cases (73.2%, 93/127) reported from January 2022 to September 2023 and 186 controls completed this questionnaire. Farmers accounted for the highest proportion (68.8%, 64/93). In multivariate logistic regression analysis, there were three significant risk factors for HFRS: piles of firewood and/or grain in residential yards (odds ratio [ OR ]=3.75, 95% CI : 2.14–6.55), mite and/or flea bites ( OR =1.83, 95% CI : 1.06–3.18) and contacting with rats and/or their excreta ( OR =1.73, 95% CI : 1.09–2.74); three variables represented significant protective factors for HFRS: frequency of sun exposure for quilts and bedding ( OR =0.41, 95% CI : 0.19–0.90), rodent control measures at home ( OR =0.50, 95% CI : 0.30–0.81) and knowing the main sources of HFRS transmission ( OR =0.58, 95% CI : 0.36–0.90). Stratified analysis revealed that the influence of these factors varied by season, with rodent contact and control measures being particularly salient during the HTNV peak season. Conclusion This study provides the first comprehensive evidence of risk and protective factors for HFRS in Qingdao, highlighting the role of rodent control, promoting comprehensive health education, environmental management, and personal protection. However, the results should be interpreted considering the study’s limitations, including a 73.2% response rate and the potential for recall bias.